Maternal mortality in adolescents - Acosta Chávez, Manuel (2022)
A revision of concepts is presented that it has more than enough adolescents' pregnancy, considered as paradigms some of those which that deserve to be revised.The maternal deaths are exposed in adolescents in one period understood among 1986 at 2002, in this lapse 30 maternal deaths of adolescents took place that he/ she makes an alive born gross rate of 7.69/0000 and one specifies of 40.92/0000 born alive.The Direct cause of maternal death in adolescents in this revision is the Septic Abortion with 33.34%, the infections with 16.66%, you Hemorrhage with 13.34% and the Toxemia with 6.66%.The main cause insinuation of maternal death in this group constitutes it the lung tuberculosis with 10.00%.The maternal deaths in adolescents are bigger as the chronological age advances (16 to 19 years).The hospital stay, where the maternal death took place in these adolescents he/she went among 0 o'clock at 48 hours, what expresses its state criticizes in that arrived.The complications that increased their state of health, favoring their death was: the anemia 19,50%, R.P.M.11.78%, toxemia 10,33% miscarries 9.39%, the complications of the childbirth with 13,91 % and those of the puerperium 6.08%.